2022
DOI: 10.1097/shk.0000000000002046
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-13 Ameliorates LPS-Induced Endothelial-to-Mesenchymal Transition and Post–acute Lung Injury Pulmonary Fibrosis by Suppressing Transforming Growth Factor-Β1 Signaling

Abstract: The pathophysiology of acute respiratory distress syndrome (ARDS) involves cytokine storms, alveolar-capillary barrier destruction, and fibrotic progression. Pulmonary interstitial fibrosis is an important factor affecting the prognosis of ARDS patients. Endothelial-to-mesenchymal transition (EndMT) plays an important role in the development of fibrotic diseases, and the occurrence of EndMT has been observed in experimental models of LPS-induced acute lung injury (ALI). Apelin is an endogenous active polypepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…The results from this study indicate that the chronic administration of apelin does not significantly improve Ang II-induced elevation in blood pressure and cardiac remodeling, indicating that apelin does not interact with AT1 receptors, although APJ receptors share high sequence similarity with AT1 receptors [6]. However, this result is not consistent with previous studies showing that the chronic administration of apelin is effective in treating preeclampsia, pulmonary arterial hypertension, and myocardial infarction-associated cardiac remodeling [21][22][23]. One possible explanation of this controversy could be due to the hypoxic conditions in those disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…The results from this study indicate that the chronic administration of apelin does not significantly improve Ang II-induced elevation in blood pressure and cardiac remodeling, indicating that apelin does not interact with AT1 receptors, although APJ receptors share high sequence similarity with AT1 receptors [6]. However, this result is not consistent with previous studies showing that the chronic administration of apelin is effective in treating preeclampsia, pulmonary arterial hypertension, and myocardial infarction-associated cardiac remodeling [21][22][23]. One possible explanation of this controversy could be due to the hypoxic conditions in those disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, patients with mild ARDS had lower Apelin levels than patients with severe ARDS, and survivors had higher Apelin levels than non-survivors ( Figure 3B ). Liu et al 45 also confirmed significantly higher serum Apelin levels in 28 patients with sepsis-related ARDS compared with 20 healthy volunteers and a higher level in survivors compared with non-survivors.…”
Section: The Involvement Of the Apelin/apj System In Septic Conditionsmentioning
confidence: 81%
“…Tissue fibrosis is typically characterized by excessive proliferation of myofibroblasts, abnormal increases, and excessive deposition of extracellular matrix (28). Pulmonary fibroblasts are the key cells that synthesize and secrete collagen into the extracellular matrix of mesenchymal tissues, and their abnormal behavior results in pulmonary fibrosis (29).…”
Section: Discussionmentioning
confidence: 99%